Effect of Composition of Iron-Cobalt Oxide Catalyst and Process Parameters on The Hydrothermal Liquefaction of Sugarcane Bagasse - Gopalakrishnan Govindasamy; Rohit Sharma; Sunu Subramanian (Bulletin of Chemical Reaction Engineering & Catalysis, 2020)
Development of catalyst with high deoxygenation activity and optimum process parameters are the key for getting the highest biooil yield with the least oxygen content by hydrothermal liquefaction. With this view, iron-cobalt oxides of Co/Fe ratio 0.33, 1.09, 2.35, and 3.52 were prepared by co-precipitation method, and characterized by XRD, BET surface area, chemical composition by EDX method, and evaluated for hydrothermal liquefaction of sugarcane bagasse in a high-pressure batch reactor under subcritical conditions using CO as process gas to find the optimum Co/Fe ratio and process parameters. Optimum Co/Fe ratio was found to be 1.09 as it gave the highest bio-oil yield of 57.6% with the least oxygen content of 10.8%, attributed to the cobalt ferrite, the major phase present in it. The optimum temperature, initial CO pressure, water/biomass ratio, catalyst/biomass ratio and reaction time for the highest oil yield with the least oxygen content were found to be 250 °C, 45 bar, 28, 0.4, and 120 min,  respectively. From the effect of reaction time, it was found that much of the hydrolysis of lignocellulose to water soluble oxygenates, its deoxygenation to bio-oil and its deoxygenation to low oxygen containing bio-oil took place in initial 15 min, 15 to 60 min, and from 30 to 120 min, respectively. Total oil yield (%) was lower by 21% and % oxygen in total oil was higher by 9.9% for spent catalyst compared to fresh catalyst indicating the erosion in the deoxygenation activity of catalyst and thus need for improving its hydrothermal stability. Copyright © 2020 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).